Sisi Sunni az-Zamakhsyarī: - Maryam Shofa Shofa (Lajnah Pentashihan Mushaf Al-Qur'an, 2011)
The leanings of az-Zamakhsyarī towards the Mu’tazili sect is clearly seen in his Qur’anic exegesis text called al-Kasysyāf. Many Islamic scholars have already identified and demonstrated the Mu’tazili sectarian tendencies of az-Zamakhsyarī. He used his expertise in the field of literature in order to present an interpretation of the Qur’an as supporting his sect’s viewpoint. However, this article will explore a different approach to demonstrate an other side of az-Zamakhsyarī. The writer will trace his interpretation in exegesis, particularly on the verses dealing with the concept of torture in the graveyard, to reveal the Sunnite side of az-Zamakhsyarī